Dynamics of major and trace elements during leaf litter decomposition in semi-arid mangrove subject to urban runoff - Robin, Sarah Louise; Alfaro, Andrea C.; Gututuauva, Kapeliele; Marchand, Cyril (Marine pollution bulletin, 2025)
This study examined the dynamics of major elements and trace metals (TM) during litterfall decomposition in two mangrove forests—control and urban—along New Caledonia's coast. A litterbag experiment was carried out for 72 days for the two main species (Rhizophora stylosa, and Avicennia marina) of the island. Results showed that the urban runoff enhances the leaching of some major elements (K, Mg, Na) during litter decomposition. The enrichment of TM in litter is also faster at the urban site. The dynamics of some major elements and TM are rather influenced by species metabolisms or element's characteristics such as Mn which does not increase in concentration in the decomposing litter. This study concludes that urban runoff accelerates the leaching of major elements and the enrichment of TM during leaf litter decomposition in mangrove forests, with species-specific factors and environmental conditions also playing significant roles in influencing these dynamics. [Display omitted] •Litterfall decomposition under the influence of urban runoff was investigated.•Stands position and species salt tolerance influence initial leaves composition.•Urban rainwater runoff enhances major elements leaching from litterfall.•Trace metal dynamics are influenced by their bioavailability in mangrove soil.•As and Mn are exceptions due to their complexations and oxidation states.